2016
DOI: 10.20960/nh.312
|View full text |Cite
|
Sign up to set email alerts
|

The association between water intake, body composition and cardiometabolic factors among children - The Cuenca study

Abstract: Introduction: Beverage consumption and its possible association with current obesity epidemic and metabolic syndrome is under investigation in recent years, however water intake is probably the most underestimated of all beverages and could play an important role. Objective: The aim of this study was to examine the association between water intake, body composition and cardiometabolic factors in a sample of Spanish children. Methods: A cross-sectional study was conducted in 366 schoolchildren (53.5% girls) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
1
5
0
2
Order By: Relevance
“…Previous literature assessing the role of hydration on exercise performance has demonstrated the detrimental impact of acute hypohydration on aerobic [ 1 , 2 , 3 ] and anaerobic [ 4 , 5 , 6 , 7 ] exercise performance, as well as cognitive function [ 8 , 9 , 10 , 11 ]. In recent years, the focus has shifted from the short-term impact of hypohydration on exercise and cognitive performance to the role that inadequate fluid intake, also termed underhydration [ 12 ], has on health-related outcomes such as obesity [ 3 , 13 , 14 , 15 , 16 , 17 , 18 ], diabetes [ 19 , 20 , 21 ], and chronic kidney disease [ 22 , 23 ]. However, the existing evidence examining the associations between underhydration on the aforementioned health-related outcomes in humans has primarily come from retrospective analyses of population-based cohort studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature assessing the role of hydration on exercise performance has demonstrated the detrimental impact of acute hypohydration on aerobic [ 1 , 2 , 3 ] and anaerobic [ 4 , 5 , 6 , 7 ] exercise performance, as well as cognitive function [ 8 , 9 , 10 , 11 ]. In recent years, the focus has shifted from the short-term impact of hypohydration on exercise and cognitive performance to the role that inadequate fluid intake, also termed underhydration [ 12 ], has on health-related outcomes such as obesity [ 3 , 13 , 14 , 15 , 16 , 17 , 18 ], diabetes [ 19 , 20 , 21 ], and chronic kidney disease [ 22 , 23 ]. However, the existing evidence examining the associations between underhydration on the aforementioned health-related outcomes in humans has primarily come from retrospective analyses of population-based cohort studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies it was found that higher consumption of water per weight was negatively associated with BMI and body fat, and obese children were less hydrated than normal peers, and they drink less water. 15,16 Compatible to other studies, we saw that these environmental factors create an obesogenic environment inducing obesity. [17][18][19] There are conflicting results in the literature about socio-economic level and frequency of obesity.…”
Section: Discussionmentioning
confidence: 58%
“…A ingestão de água é considerada uma prática de saúde, visto que sua falta (desidratação) pode influenciar na concentração, vigilância e memória de curto prazo e ocasionar problemas como cefaleia e litíase urinária 28 . Além disso, a ingestão adequada tem sido associada ao menor consumo energético, o que pode contribuir na prevenção da obesidade e síndrome metabólica 6,29 .…”
Section: Discussionunclassified